Outdoor enthusiasts’ perspectives on livestock animal treatment - Elizabeth Byrd; Nicole Olynk Widmar (Journal of Global Business Insights, 2017)
Demand for pork chops and chicken breasts were analyzed using best-worst scaling and consumer choice experiments. Outdoor enthusiasts (who regularly hunt, fish, or participate in outdoor activities), which represent a unique consumer group with respect to livestock animal welfare, were surveyed with respect to meat purchasing attributes. Six meat attributes were analyzed for relative levels of preferences with safety having the largest share. Nutrition and taste were more important to outdoor enthusiasts than a representative sample of U.S. residents. Positive and significant mean willingness to pay estimates were obtained with the exception of locally produced pork chops. Outdoor enthusiasts were willing to pay a higher amount for retailer and industry verified antibiotic free pork chops than a representative sample of U.S. consumers.